Pathogenetic therapeutic approaches for endocrine diseases based on antisense oligonucleotides and RNA-interference - Olga Golounina; Ildar Minniakhmetov; Ramil Salakhov; Rita Khusainova; Ekaterina Zakharova; Igor Bychkov; Natalia Mokrysheva (Frontiers in Endocrinology)
Molecular therapy uses nucleic acid-based therapeutics agents and becomes a promising alternative for disease conditions unresponsive to traditional pharmaceutical approaches. Antisense oligonucleotides (ASOs) and small interfering RNAs (siRNAs) are two well-known strategies used to modulate gene expression. RNA-targeted therapy can precisely modulate the function of target RNA with minimal off-target effects and can be rationally designed based on sequence data. ASOs and siRNA-based drugs have unique capabilities for using in target groups of patients or can be tailored as patient-customized N-of-1 therapeutic approach. Antisense therapy can be utilized not only for the treatment of monogenic diseases but also holds significant promise for addressing polygenic and complex diseases by targeting key genes and molecular pathways involved in disease pathogenesis. In the context of endocrine disorders, molecular therapy is particularly effective in modulating pathogenic mechanisms such as defective insulin signaling, beta-cell dysfunction and hormonal imbalances. Furthermore, siRNA and ASOs have the ability to downregulate overactive signaling pathways that contribute to complex, non-monogenic endocrine disorders, thereby addressing these conditions at their molecular origin. ASOs are also being studied worldwide as unique candidates for developing therapies for N-of-1 therapies. The sequence-specific ASOs binding provides exceptional accuracy in N-of-1 approaches, when the oligonucleotide can be targeted to a patient’s exact mutant sequence. In this review we focus on diseases of the endocrine system and discuss potential RNA-targeted therapeutic opportunities in diabetes mellitus, including monogenic beta cell diabetes, and obesity, including syndrome obesity and monogenic obesity, as well as in non-monogenic or complex endocrine disorders. We also provide an overview of currently developed and available antisense molecules, and describe potentials of antisense-based therapeutics for the treatment of rare and «ultrarare» endocrine diseases.